Politique publique et développement des chaînes alimentaires courtes de proximité : une analyse des PDR de la Région Occitanie - Fredéric Wallet; Melise Dantas Machado Bouroullec (Développement Durable et Territoires)
This article analyzes the place of short local chains (SLC) in rural development policy (RDP) in Occitanie Region. We identify measures related to SLCs through a textual analysis of the Midi-Pyrenees and Languedoc-Roussillon 2014-2020 PDRs and their respective calls for projects. The results underline a timid support but more marked in Languedoc-Roussillon. The contours of the future CAP (decrease in the budget, transition to a single national strategic plan, etc.) will condition the autonomy left to the Regions to define support measures for SLCs adapted to local requirements. In addition to support for physical investments, installation and cooperation, training and networking of actors in the territory should be supported.